The Water Area of Sawa Lake as Derived from Land Surface Temperature and Remote Sensing Data - Radeef, Haidar A.; Abdulameer, Inbethaq M-Ali (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Sawa Lake is one of the unique lakes in Iraq. It is located in the southwestern part of Iraq. It is one of the closed lakes, as no surface water source works to feed the lake. The lake feeds on groundwater. The source of this groundwater is the Dammam Basin. During the past ten years, The lake has had many changes, which led to a decrease in water levels. This also led attention to study of the causes of these changes. Many types of research were presented in the study of the state of the lake. This research used remote sensing images from Landsat 8 OLI to monitor the changes during 2020-2021 by applying the NDWI equation to extract water area from image data. The results of the areas were obtained from a special report by Normalized Difference Water Index (NDWI). Then, the lake surface water temperature was derived from Landsat 8 thermal bands (TIRS). The lake water area and temperatures increased in summer and decreased in winter and autumn. Then, it is not the main reason for the change in the lake water area. The levels of the lake water rise during the dry period and decrease during the rainy period. The natural factors have little influence in reducing the lake water. It is attributed to human factors, groundwater depletion, and a reduction in water supply from the Dammam Basin, which feeds the lake.